2014
DOI: 10.1038/ncomms4470
|View full text |Cite
|
Sign up to set email alerts
|

A general ligand design for gold catalysis allowing ligand-directed anti-nucleophilic attack of alkynes

Abstract: Most homogenous gold catalyses demand ≥0.5 mol % catalyst loading. Due to the high cost of gold, these reactions are unlikely to be applicable in medium or large scale applications. Here we disclose a novel ligand design based on the privileged biphenyl-2-phosphine framework that offers a potentially general approach to dramatically lowering catalyst loading. In this design, an amide group at the 3’ position of the ligand framework directs and promotes nucleophilic attack at the ligand gold complex-activated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(68 citation statements)
references
References 52 publications
1
65
0
2
Order By: Relevance
“…An additional notable example has been reported by Zhang et al with the introduction of a basic center in the ligand, in order to direct and promote the nucleophilic attack on the coordinated UHC. 22 In an exhaustive work by Wang et al, 23 the authors experimentally categorized gold-catalyzed reactions and they found that reactions for which the rate-determining step (RDS) is the nucleophile attack are favored by electron-withdrawing ligands which, in contrast, give lower catalytic activities when the protodeauration step is the RDS.…”
Section: ■ Introductionmentioning
confidence: 98%
“…An additional notable example has been reported by Zhang et al with the introduction of a basic center in the ligand, in order to direct and promote the nucleophilic attack on the coordinated UHC. 22 In an exhaustive work by Wang et al, 23 the authors experimentally categorized gold-catalyzed reactions and they found that reactions for which the rate-determining step (RDS) is the nucleophile attack are favored by electron-withdrawing ligands which, in contrast, give lower catalytic activities when the protodeauration step is the RDS.…”
Section: ■ Introductionmentioning
confidence: 98%
“…The synthetic and characterization procedures have been described in detail in previous reports [11,27]. …”
Section: Preparation and Characterization Of Catalystmentioning
confidence: 99%
“…Several years later, R 3 PAuX (X = trifluoromethanesulphonate, OTf − ) or other weakly coordinating counter ions) demonstrated excellent catalytic performance in Conia-ene [19,20] and hydroarylation [21][22][23] reactions, as well as several carbon-heteroatom bond-forming reactions [24][25][26]. Recently, Zhang's group designed a new complex with the ligand (1,1 -biphenyl)-2-ylphosphine, which was found to be effective in the reaction of acid and alkynes with a turnover number up to 99,000 [27]. In previous articles, we also reported gold complexes with Mor-Dalphos ligands, which show excellent catalytic performance in the synthesis of 2,4-disubstituted thiazoles from terminal alkynes and thioamides [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…13 On the other hand, these ligands have found extensive utility in homogeneous gold catalysis, 14 although Au(I) complexes typically assume a distinctively different linear structure. To this end, there exist enormous yet largely untapped opportunities 15 for the development of novel gold catalysis based on new biphenyl-2-ylphosphine ligands specifically tailored to accommodate the linear Au(I) complexes. Our simple structural modeling revealed, as shown in Figure 1D, that with bulky groups on phosphorus gearing the P–Au–alkyne centroid axis parallel to the pendant phenyl ring the C–C triple bond would lie roughly at the same level as the line defined by C3′ and C5′, suggesting that functionalization of these positions and C4′ would offer unique and potentially novel reactivities to gold chemistry.…”
mentioning
confidence: 99%